Răspuns :
tg(a+b)=[tex] \frac{tga+tgb}{1-tgatgb} [/tex].
Deci tg(x+π/3)=[tex] \frac{tgx+tg \frac{ \pi}{3} }{1-tgxtg \frac{ \pi}{3}} = \frac{ \frac{1}{2} + \sqrt{3} }{1- \frac{ \sqrt{3} }{2} }= \frac{1+2 \sqrt{3} }{2- \sqrt{3}}=8+ 5\sqrt{3} [/tex], dupa ce rationalizam numitorul, amplificand fractia cu 2+√3.
Deci tg(x+π/3)=[tex] \frac{tgx+tg \frac{ \pi}{3} }{1-tgxtg \frac{ \pi}{3}} = \frac{ \frac{1}{2} + \sqrt{3} }{1- \frac{ \sqrt{3} }{2} }= \frac{1+2 \sqrt{3} }{2- \sqrt{3}}=8+ 5\sqrt{3} [/tex], dupa ce rationalizam numitorul, amplificand fractia cu 2+√3.